Barriers to and Facilitators of Interprofessional-Interdepartmental Interventions: Unearthing Departmental Culture. (March 2015) - Michalec, Barret; Reinhold, Natalie; Dressler, Robert; Laskowski-Jones, Linda; Adarve, Laura; Elliott, Daniel
This study evaluates how emergency department (ED) and medical intensive care unit (MICU) providers interact in the setting of a quality improvement project designed to enhance transport/care for patients from the ED to the MICU. Focus groups were conducted with nurses, residents, physician assistants, and physicians from the ED and MICU at baseline and 6 months regarding their thoughts on and perspectives of the intervention and working with colleagues from another department. Data were then analyzed utilizing a multistep coding scheme that identified key barriers to and facilitators of the interprofessional-interdepartmental intervention. Analysis also showed, however, that variances in departmental culture play a significant role in the willingness and ability of providers to practice interdepartmental team-based care. It is argued that anticipating and acknowledging these differences and designing systems to address them prior to launch will be essential to the development and implementation of effective interdepartmental quality improvement interventions.